Failing the test or the failure of the test: The case of environmental education in Israel - Zuzovsky, Ruth (Education Policy Analysis Archives, 2021)
Different approaches are employed when teaching environmental issues. One approach, termed the “environmental scientific approach,” perceives environmental education as part of life or earth sciences, providing factual, scientific knowledge. Another approach, termed the “environmental sustainability citizenry approach”, emphasizes sustainability and balancing between the need to move forward technologically and economically and the need to protect the environments in which we and others live. A synthesis of the two approaches encompasses both environmental scientific literacy and environmental sustainability citizenry. This article examines the degree to which changes in the emphasis given to the two approaches worldwide and in Israel impacted the achievements of Israeli eighth graders in this field. Based primarily on data from the Third Mathematics and Science Study-(TIMSS), the findings indicate that the TIMSS tests were biased toward the “environmental scientific” approach, in contrast to the more recent and accepted trends of the “environmental sustainability citizenry approach” embedded in Israeli curriculum. The assessment of environmental achievements in Israel, that was based on the biased test of the TIMSS study, fails to accurately reflect both the curricular changes that have taken place in Israel in this field and students' achievements, thus rendering this assessment inappropriate for this purpose.